Amílcar Cabral and Amartya Sen: Freedom, Resistance and Radical Realism. Issue 167 (1st June 2021) - Hamilton, Lawrence
Abstract: This article compares the ideas of Amílcar Cabral and Amartya Sen on capability, freedom, resistance and political change, thereby revealing the importance of radical realism in political thought and development studies. Sen's path-breaking work has been transformative for multiple disciplines, not least development. Yet, reading Sen alongside the ideas of one of Africa's most successful anti-colonial political leaders is revelatory: it provides the basis for the argument that radical realism is most valuable if it is action-guiding, comparative and about context-specific change. This involves a distinction between realistic political theory and realism in political thought where only the latter demands utopian thinking. What follows from this regarding democracy, impartiality and justice? In answering this with reference to some social movements, the article then defends the political potential of conflict, partisan positions, resistance and political change directed towards overcoming domination.